The Effect of Incentives and Work Facilities on Job Loyalty with Employee Satisfaction as a Mediation Variable at PT. Samudera Indonesia Jambi - Nila Putria; Arthur Sitaniapessy; Joko Rizkie Widokarti (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to analyze the effect of incentives and work facilities on job loyalty with employee satisfaction as a mediating variable at PT. Samudera Indonesia. This research employed a quantitative approach using the SEM-PLS method. Data were collected through questionnaires and interviews involving 92 employees selected using probability sampling techniques. The research instrument used a Likert scale. The results showed that incentives and work facilities have a positive and significant effect on employee satisfaction and job loyalty. Employee satisfaction also has a positive effect on job loyalty and mediates the influence of incentives and work facilities on job loyalty. This study concludes that providing proper incentives and adequate work facilities can improve employee satisfaction and strengthen employee job loyalty within the organization.